CD56+ immune cell infiltration and MICA are decreased in breast lobules with fibrocystic changes - Kerekes, Daniel (Breast Cancer Res Treat, 2017)
PURPOSE: While the role of natural killer (NK) cells in breast cancer therapy has been investigated, little information is known about NK cell function and presence in nonmalignant and premalignant breast tissue. Here, we investigate and quantify NK cell marker CD56 and activating ligand MICA in breast tissue with benign breast disease. METHODS: Serial tissue sections from 88 subjects, 44 with benign breast disease (BBD) who remained cancer-free, and 44 with BBD who later developed cancer, were stained with H&E, anti-MICA, and anti-CD56. Up to ten representative lobules were identified on each section. Using digital image analysis, MICA and CD56 densities were determined for each lobule, reported as percent of pixels in the lobule that registered as stained by each antibody. Analyses were performed on a per-subject and per-lobule basis. RESULTS: Per-subject multivariate analyses showed associations of CD56 and MICA with age: CD56 was increased in older subjects (p = 0.03), while MICA was increased in younger subjects (p = 0.005). Per-lobule analyses showed that CD56 and MICA levels were both decreased in lobules with fibrocystic change, with median levels of CD56 and MICA staining, respectively, at 0.31 and 7.0% in fibrocystic lobules compared to 0.76 and 12.2% in lobules without fibrocystic change (p < 0.001 for each). Among fibrocystic lobules, proliferative/atypical lobules showed significantly lower expression compared to nonproliferative lobules for MICA (p = 0.02) but not for CD56 (p = 0.80). CONCLUSION: Levels of CD56+ NK cells and activating ligand MICA were decreased in breast lobules with fibrocystic change, and MICA levels showed a significant stepwise decrease with increasing histopathologic abnormality. MICA levels were also significantly decreased in older subjects, who generally have higher risk of developing cancer. These findings advance a model in which MICA promotes cytotoxic activity in CD56+ NK cells to protect against tumorigenesis in breast lobules, and suggest further research is warranted. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10549-017-4558-0) contains supplementary material, which is available to authorized users.